Pentahelix-Based Development Strategy of Batu Sori Tourism Object in Lea-Lea Sub-district, Baubau City - Fendi Satria Ramadani; Asmiddin, Asmiddin; La Didi (Sean Institute, 2024)
The purpose of this research is to explore the pentahelix-based Batu Sori tourist attraction development strategy in Lea-Lea District, Baubau City which includes SO (Strength - Opportunity) strategy, WO (Weakness - Opportunity) strategy, ST (Strength - Threat) strategy and WT (Weakness - Threat) strategy. And the role of pentahelix stakeholders in the development of Batu Sori tourism. The method used in this research is qualitative description. Data were collected through interviews, questionnaires, observation and documentation. The informants in this study were 10 people. The data was analysed using excel application. The results showed first that SWOT mapping, placing pentahelix-based Batu Sori tourism development in the Aggressiveness situation, namely tourism has a number of elements of strength as well as opportunities that are high enough to realise the development strategy of the pentahelix-based Batu Sori tourist attraction in Lea-Lea Kec Baubau City, so that the development strategy that must be pursued is that all strengths must be maximised by taking advantage of existing opportunities. Second, the development of a number of alternative aggressiveness strategies formulated for the development of Batu Sori tourism, including, 1) Maximising the potential of existing natural beauty and the use of social media and digital platforms, 2) Maximising opportunities to establish partnerships with private parties / entrepreneurs, 3) Batusori managers need to hold events or festivals. Furthermore, the role of penta helix stakeholders in Batu Sori tourism development in Baubau City can be optimised through the government, academics, the community, business people, and the media. The government plays an important role in planning and regulating policies that support the development of tourism infrastructure, as well as providing incentives for investors or private parties.